Accounting Skills in Practice and Their Impact on Employability: A Curriculum Review in an Autonomous Philippine University - Micabalo, Kingie; Poliquit, Winnie Marie; Ibañez, Estela; Cartalla, Kyla Flor; Calimpong, Romielyn (JPAIR Institutional Research, 2021)
As competition for graduate jobs increases, students need to consider new ways to differentiate from equally qualified and skilled candidates. The investigation determined the significance of a curriculum in the working environment and graduates' employability. The examination contrived a sum of 169 respondents on a snowball testing strategy. Frequency and simple percentage, weighted mean, Chi-Square Test of Independence, and One way ANOVA was utilized to treat the data. The findings revealed that communication skills, basic accounting skills, & financial reporting skills are among the essential skills to acquire to serve a spot on the labor market. The investigation further revealed a significant association on civil status, length of time to get a job after graduation, Nature of work on the first and current job, work status, graduate studies, and the degree of enhancement the graduates suggested to meet the demands of the profession. It also revealed a statistically significant distinction following the respondents' profile when grouped by its influence on the proposed program enhancement suggested by the graduates. The study concluded that maximizing graduates' employability, the viability of curriculum enhancement and teaching methodologies, and necessary facilities must be concentrated to depict the utmost realization of objectives and goals of the program. It further concludes that a strong partnership with an internship program can increase alignment between educators, students, and industries.
Keywords: Business and accountancy; employability; descriptive- correlational; Mandaue City; Philippines